The Effect of Professionalism, Independence, And Professional Ethics on Auditor Performance at Public Accounting Firms (PAFS) In Medan, North Sumatra - Desi Maya Isnaini; Ribka Yolanda Septialita Naibaho; Afrizar Pane; Muhammad Fahmi (Sean Institute, 2026)
This study aims to examine and analyze the influence of professionalism, independence, and professional ethics on auditor performance at public accounting firms (PAFs) in Medan, North Sumatra. This study employs a quantitative method with a causal-comparative approach to identify the cause-and-effect relationship between independent and dependent variables. The data used in this study are primary data obtained through the distribution of questionnaires to permanent auditors at Public Accounting Firms in Medan. The population in this study consists of all permanent auditors working at Public Accounting Firms in Medan, with a sample size at 40 respondents determined using a saturation sampling technique. This study indicates that Professionalism, Independence, and Professional Ethics simultaneously have a significant effect on Auditor Performance. Partially, Professionalism, Independence, and Professional Ethics have a significant effect on Auditor Performance.